Influence of ingredient and preparation process on the microstructure of TZC molybdenum alloys - ZHOU Hongdeng; XU Wenjin; TIAN Qingchao (Fenmo yejin jishu, 2025)
Different sintering and hot-pressing processes were employed to prepare the TZC alloys doped by TiH2/ZrH2 and TiC/ZrC, respectively. The microstructure evolution and composition distribution of the alloys under the different processing conditions were studied by optical metallographic observation, scanning electron microscopy, and phase analysis. The results show that the phase constituents of these two doping are basically the same. Comparison with that of the TZC alloys doped by TiH2/ZrH2, the density of the TZC alloys doped by TiC/ZrC after sintering increases from 9.21 g·cm−3 to 9.68 g·cm−3, and the hardness increases from HV 210 to HV 245, respectively. Hot pressing after sintering significantly increases the density and hardness of the alloys, and the grain distribution changes from the bimodal distribution in the sintered state to the unimodal distribution. It is found that the phase structures of these two doping undergo transformation during the high-temperature sintering, which determines the reaction diffusion process and thereby affects the density and hardness. The TZC alloys doped by TiH2/ZrH2 form the different characteristic regions in the microstructure after hot pressing, and the TZC alloys doped by TiC/ZrC with fine grain, high relative density, and high hardness can be directly obtained by hot-pressing.